Progress in studies on Central Asian foci of zoonotic cutaneous leishmaniasis: a review - Strelkova, M V (Folia parasitologica, 1996)
In this paper, studies on zoonotic cutaneous leishmaniasis (ZCL) are reviewed that were performed during the last ten years largely by scientists of the Martsinovsky Institute of Medical Parasitology and Tropical Medicine. New data on the taxonomy of Leishmania circulating in populations of Rhombomys opimus, their main host, and the results of field and laboratory studies allowed revision of certain concepts generally accepted in epidemiology and epizootology of ZCL in Central Asia.
Keywords: Animals; střední Asie; Leishmaniasis, Cutaneous; Zoonoses; lidé; leishmanióza kožní; zvířata; zoonózy; Leishmania; Asia, Central; Humans